2007
DOI: 10.1185/030079908x253807
|View full text |Cite
|
Sign up to set email alerts
|

Use of 2-octyl cyanoacrylate for skin closure of sternal incisions in cardiac surgery: observations of microbial barrier effects

Abstract: From the patient records reviewed in this study, it was found that the routine use of 2-octyl cyanoacrylate as an add-on measure to conventional sutures was associated with a significant reduction in infection rates for cardiovascular surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Grauhan et al grouped deep and superficial wound infections together and reported a significant reduction in SSI in the cyanoacrylate glue‐sealed Donati sutures (two superficial infections) compared with the control group using subcuticular sutures alone (seven superficial infections +two deep infections) ( P < 0.05). In a large retrospective study of 1360 of patients undergoing cardiac surgery, Souza et al reported a significant reduction ( P < 0.001) in the incidence of SSI (superficial and deep) in the intervention group using additional cyanoacrylate glue (2.1%) compared with the control group (4.9%) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grauhan et al grouped deep and superficial wound infections together and reported a significant reduction in SSI in the cyanoacrylate glue‐sealed Donati sutures (two superficial infections) compared with the control group using subcuticular sutures alone (seven superficial infections +two deep infections) ( P < 0.05). In a large retrospective study of 1360 of patients undergoing cardiac surgery, Souza et al reported a significant reduction ( P < 0.001) in the incidence of SSI (superficial and deep) in the intervention group using additional cyanoacrylate glue (2.1%) compared with the control group (4.9%) …”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective study of 1360 of patients undergoing cardiac surgery, Souza et al reported a significant reduction (P < 0.001) in the incidence of SSI (superficial and deep) in the intervention group using additional cyanoacrylate glue (2.1%) compared with the control group (4.9%). 25 In paediatric surgery, Romero et al assessed the use of subcuticular suture and either cyanoacrylate glue or Steri-Strips ® in the closure of laparoscopic ports after laparoscopic appendectomy. 26 A single case of SSI occurred in the Steri-Strips ® group-no significant difference was identified in the incidence of SSI.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
“…11 Souza et al, found that routine use of topical adhesive for wound closure decreased the infection rates when used as an add-on measure to conventional sutures, with a significant reduction in infection rates for cardiovascular surgery patients. 12 Recently a comparative study conducted by Ando M et al, wound closure with staples was compared with 2-octyl cyanoacrylate. 8 out of 294 patients in the metal-staple group compared with none of 315 patients in the 2-octyl cyanoacrylate group acquired surgical site infections (SSIs) (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Имеются также данные исследований об анти-микробных свойствах самого клея и эффективности совместного использования клея в комплексе мер профилактики ИОХВ [11,22].…”
Section: Discussionunclassified